Discourse Analysis of Turkish History Textbooks: The Case of Greek-Turkish Relations in the Book Çağdaş Türk ve Dünya Tarihi - Παπαοικονόμου Αντώνης (Education Sciences, 2025)
The analysis of the Turkish history textbook "Çağdaş Türk ve Dünya Tarihi" reveals how Greek-Turkish relations are presented with an emphasis on a fanatical and nationalistic perspective. The textbook focuses on the main issues of these relations: Western Thrace, the Aegean islands, Cyprus, and the continental shelf. Regarding the continental shelf issue, the textbook accuses Greece of starting the dispute by granting oil exploration licenses, while portraying Turkey as reactive and seeking negotiations based on international law. The FIR problem is also presented as a result of Greece's actions, with Turkey reacting passively. The militarization of the Aegean islands by Greece and its desire to extend territorial waters are considered threats to Turkey's national security. Finally, the issue of the Turkish minority in Western Thrace is highlighted with emphasis on Greece's violations of rights, without mentioning the cultural differences of the minorities. The Cyprus issue is presented with the Greek Cypriots being responsible for the tension, while Turkey is portrayed as the defender of Turkish Cypriot rights.